Economic Transformation To Get Out of the Middle Income Trap Condition To Reach Indonesia Gold 2045 - Maryanti, Sri; Widayat, Prama; Lubis, Nurhayani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2023)
Objectives – The article aims to analyze whether the Economic Transformation carried out by Indonesia will be able to get Indonesia out of the Middle Income Trap (MIT). And whether through economic transformation is able to realize a Golden Indonesia 2045. Methodology- In this study, the method used is descriptive and literature study where in descriptive analysis data and information will be displayed by comparing several countries that were originally included in middle-income countries such as Malaysia, China and Thailand as well as high-income countries such as Japan and South Korea. The data and information collected are taken from 1970-2021 from various sources. In this study, the method used is descriptive and literature study where in descriptive analysis data and information will be displayed by comparing several countries that were originally included in middle-income countries such as Malaysia, China and Thailand as well as high-income countries such as Japan and South Korea. The data and information collected are taken from 1970-2021 from various sources. Findings – In the short term, Indonesia must accelerate capital accumulation through accelerated investment, especially related to infrastructure, in order to encourage economic growth above 6%. In the medium term, it must develop, utilize innovation and technology in order to increase Total Factor Productivity (TFP). The economic transformation carried out by Indonesia is focused on the triggering factors and 4 (four)